Social and geographical factors affecting access to treatment of colorectal cancer: a cancer registry study. Issue 2 (24th April 2012) - Crawford, S Michael; Sauerzapf, Violet; Haynes, Robin; Forman, David; Jones, Andrew P
Abstract : Objective: Cancer outcomes vary between and within countries with patients from deprived backgrounds known to have inferior survival. The authors set out to explore the effect of deprivation in relation to the accessibility of hospitals offering diagnostic and therapeutic services on stage at presentation and receipt of treatment. Design: Analysis of a Cancer Registry Database. Data included stage and treatment details from the first 6 months. The socioeconomic status of the immediate area of residence and the travel time from home to hospital was derived from the postcode. Setting: Population-based study of patients resident in a large area in the north of England. Participants: 39 619 patients with colorectal cancer diagnosed between 1994 and 2002. Outcomes measured: Stage of diagnosis and receipt of treatment in relation to deprivation and distance from hospital. Results: Patients in the most deprived quartile were significantly more likely to be diagnosed at stage 4 for rectal cancer (OR 1.516, p<0.05) but less so for colonic cancer. There was a trend for both sites for patients in the most deprived quartile to be less likely to receive chemotherapy for stage 4 disease. Patients with colonic cancer were very significantly less likely to receive any treatment if they came from any but the most affluent area (ORs 0.639, 0.603 and 0.544 in increasingly deprived quartiles), this may have been exacerbated if the hospital was distant from their residence (OR for forth quartile for both travel and deprivation 0.731, not significant). The effect was less for rectal cancer and no effect of distance was seen. Conclusions: Residing in a deprived area is associated with tendencies to higher stage at diagnosis and especially in the case of colonic cancer to reduced receipt of treatment. These observations are consistent with other findings and indicate that access to diagnosis requires further investigation.